Efficacy of lidocaine spray for pain relief during endometrial sampling: A double blind randomized controlled trial - Jakkabut, Patom; Maneechot, Napafun (Journal of Medical and Public Health Region 4, 2026)
This research aims to study the effectiveness of a 10% lidocaine spray for pain reduction during endometrial sampling using a Wallach Endocell. This randomized controlled trial was conducted at the gynecology outpatient department of Phrae Hospital from October 2023 to February 2024. The sample group consisted of 64 women with an indication for endometrial sampling. Participants were divided into two groups: the experimental group, which received a 10% lidocaine spray (40 mg, 4 sprays) to the cervical surface before the procedure, and the control group, which received a 0.9% saline spray. Pain was assessed using a 10 cm Visual Analogue Scale. Data collection tools included three parts: Part 1 for personal patient information, Part 2 for pain levels, and Part 3 for observing adverse drug reactions and monitoring for severe allergic reactions. The study found no significant differences in the general characteristics of the two groups. However, pain scores were significantly lower (p < 0.05) in the group that received the 10% lidocaine spray compared to the control group. Specifically, pain scores were 3.0 ± 1.3 and 3.8 ± 1.6, respectively, after tenaculum placement, and 3.0 ± 1.3 and 5.3 ± 1.9, respectively, during the tissue sampling, both of which were statistically significant (p < 0.05). Pain scores also remained significantly lower 15 minutes after the procedure. However, at 30 minutes post-procedure, there was no statistically significant difference in pain scores between the lidocaine group (0.22 ± 0.5) and the control group (0.5 ± 0.8) at the 0.05 level.